OneRice breeding strategy - CGIAR Research Program on Rice (2021)
The breeding programs and the Integrative Research Platform of IRRI have initiated resource planning and activities based on the OneRice breeding strategy. The varietal creation and dissemination work flows have been optimized and will be continuously improved to gain operational efficiency and speed driving genetic gains in the breeding program.